Analyzing the Influence of Dividends on Share Prices in the Iraqi Stock Market from (2010 - 2020) - Sabri, Hivi Azeez; Salih , Bahram Mahmood; Omar , Hivi Malu (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
This study examines the relationship between dividend policies and stock prices among companies listed on the Iraq Stock Exchange from 2010 to 2020. This study utilizes a descriptive analytical approach, drawing on data from annual financial statements and disclosures published by the Iraq Stock Exchange. This study employs a simple linear regression model to analyze the impact of dividends per share and retained earnings per share on the market share price. The findings indicate a negative, statistically insignificant relationship between cash dividends and share prices, whereas retained earnings show a direct positive and significant correlation with stock valuations. Prior research in the Iraqi context has identified cash liquidity as the main determinant of dividend payout decisions, with shareholders favoring regular distributions, regardless of ownership. Studies also find a positive link between profit retention, investment opportunities, and dividends. However, broader challenges facing emerging stock exchanges, such as underperformance, speculation, and a lack of investor knowledge, can negatively impact market performance. This study provides a comprehensive, long-term analysis of dividend payout-stock price dynamics in the Iraqi market, offering valuable insights into how this relationship manifests in an emerging economy setting. The results contribute to the theoretical understanding of the factors driving stock valuation, and have practical implications for investment strategies and corporate dividend policies in Iraq and similar markets. Key recommendations include advertising campaigns to encourage savings, providing investment advisory services, and improving financial disclosure to build investor confidence.